2020
DOI: 10.1111/rsp3.12366
|View full text |Cite
|
Sign up to set email alerts
|

The informal sector and Covid‐19 economic impacts: The case of Bahia, Brazil

Abstract: This paper aims to simulate the economic impacts of the withdrawal of informal workers from the labour market due to the social isolation policy implemented during the Covid-19 pandemic in Bahia state, Brazil, where 66% of workers work in the informal sector. We also consider the government income compensation policy to make up part of their income. The partial hypothetical extraction method was used in a regional input-output matrix, base year 2012 with 42 economic sectors. Our simulations show that the withd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 26 publications
1
29
0
1
Order By: Relevance
“…In a study carried out in Bahia, the high burden of the disease was associated with the worst living conditions of the population, whose lethality was 1.4 times higher in municipalities with high social vulnerability when compared to those with low social deprivation ( de Souza et al, 2020a ). This context reflects the need to consider the social determinants of health in plans for coping with the disease ( de Souza et al, 2020a ; de Souza et al, 2020b ; Ferreira dos Santos et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study carried out in Bahia, the high burden of the disease was associated with the worst living conditions of the population, whose lethality was 1.4 times higher in municipalities with high social vulnerability when compared to those with low social deprivation ( de Souza et al, 2020a ). This context reflects the need to consider the social determinants of health in plans for coping with the disease ( de Souza et al, 2020a ; de Souza et al, 2020b ; Ferreira dos Santos et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of the transmission dynamics and the difficulties in facing the pandemic in the state of Bahia are even greater when we consider the following points: i. 66% of the workers in Bahia work in the informal market ( Ferreira dos Santos et al, 2020 ), not only hampering the adoption of social distance measures, but demanding greater economic support from the government; ii. The high territorial dimension of the state and the number of municipalities impose challenges to local management, both in the provision of tests for the diagnosis of the disease and in hospital beds; iii.…”
Section: Discussionmentioning
confidence: 99%
“…51 Each item is rated on a fourpoint scale (based on severity) ranging from 0 for not at all to 3 for nearly every day. 50 In this study, the severity of depressive symptoms was grouped based on the overall scores ranging from 0 to 27 and classified as no/minimal (0-4), mild (5-9), moderate (10)(11)(12)(13)(14), moderately severe (15)(16)(17)(18)(19), and severe depression (20)(21)(22)(23)(24)(25)(26)(27). The online version of the questionnaire is available here: https://patient.…”
Section: Data Collection Tools and Proceduresmentioning
confidence: 99%
“…14 Several studies around the world reported a wide range of magnitude of depression among the public since the COVID-19 outbreak. The prevalence of depression among the general population was reported to be 20.1-48.3% in China, [15][16][17] 22.1% in the UK, 18 27.8% in the United States, 19 14.1% in India 20 and 67.1% in Egypt. 21 In a study done in Addis Ababa, Ethiopia, the prevalence of depression in an urban community was reported to be 12.4%.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly relevant for forecasting policy decisions to support regions experiencing COVID-19 pandemic-induced crises . We model the main contingency measures adopted by local governments-reducing the economic activity of specific sectors according to the level of risk and social distance (Santos et al, 2020;Ponce, 2020)-on the IRIO system.…”
Section: Introductionmentioning
confidence: 99%